2015
DOI: 10.3109/13880209.2015.1008148
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic potential of salvianolic acid B in multiple low-dose streptozotocin-induced diabetes

Abstract: Context: Salvianolic acids are the most abundant water-soluble compounds extracted from the herb Salvia miltiorrhiza L. (Lamiaceae) with antioxidant and protective effects. Objective: This study evaluates the antidiabetic effect of salvianolic acid B (Sal B) in multiple low-dose streptozotocin (MLDS)-induced diabetes in rat. Materials and methods: Rats were divided into control, Sal B40-treated control, diabetic, Sal B20-, and Sal B40-treated diabetic groups. Sal B was daily administered at doses of 20 or 40 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…More and more evidences indicate that Sal B exerts multiple beneficial effects on the metabolic syndrome and type 2 diabetes [17][18][19][20], although its extensive action mechanism is not clear. In this study, Sal B significantly decreased fasting blood glucose and lipid levels, and improved insulin sensitivity in db/db mice with similar effectiveness as metformin, which were consistent with our previous reports of Sal B in type 2 diabetic rats and dietinduced obese mice [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more evidences indicate that Sal B exerts multiple beneficial effects on the metabolic syndrome and type 2 diabetes [17][18][19][20], although its extensive action mechanism is not clear. In this study, Sal B significantly decreased fasting blood glucose and lipid levels, and improved insulin sensitivity in db/db mice with similar effectiveness as metformin, which were consistent with our previous reports of Sal B in type 2 diabetic rats and dietinduced obese mice [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Although its most common use is in the treatment of cardio-cerebral vascular diseases [14][15][16], Sal B is recently reported to possess a number of potential implications in the treatment of insulin resistance, obesity, and type 2 diabetes [17][18][19][20]. Sal B or Salvia miltiorrhiza extract improved glycemic control, dyslipidemia, and insulin sensitivity in high fat diet and streptozocin-induced type 2 diabetic rats [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to reduce complications of diabetes such as increased urinary albumin excretion, plasma creatinine and blood urea nitrogen levels (28), as well as diabetic nephropathy (29,30). S. miltiorrhiza has also shown a significant anti-diabetic effect in animal studies; for instance, it decreases FBG and increases the insulin sensitivity index (31,32). It is effective for preventing and treating diabetic complications such as myocardial malfunction (33,34) and diabetic retinopathy (35).…”
Section: Discussionmentioning
confidence: 99%
“…[11,12] Recent studies also reported a potential implication of Sal B in the treatment of insulin resistance, obesity, and type 2 diabetes. [13][14][15][16] In hepatocytes, Sal B has been reported a strong ability to protect cells from injury induced by oxidative stress, in ammation and enhance hepatic differentiation. [17][18][19] However, the effect of Sal B on improving hepatic lipid disorder is rarely reported.…”
Section: Introductionmentioning
confidence: 99%